An Analysis of the Determinants of Systemic Banking Crises in Southeast European Countries - Željka Asanović (Journal of Central Banking Theory and Practice, 2018)
The purpose of this paper is to determine potential indicators of systemic banking crises in five Southeast European countries. Although signal horizon in the literature usually implies a period of 12 months before and 12 months after a crisis outbreak, models in this paper imply a 24-month pre-crisis period. Probability of a banking crisis occurrence is calculated using logit regression. Results have shown that banking system indicators have higher impact on probability of systemic banking crisis occurrence compared to macroeconomic indicators, and that the banking systems of these countries are significantly exposed to global trends.
Keywords: G01; C23; C25; 330; determinants of systemic banking crises; logit regression; Southeast European countries